Design of a constant current relaxation oscillator (voltage controlled) with improved PVT tolerance - Tan, Chong Boon (Nanyang Technological University, 2020)
Modern mobile technology has added difficult caveats to any circuits built to operate within them. Any such circuit has to be operable across a wide spectrum of environmental conditions, powered by a battery with limited power, low voltage and potential dips as power depletes, as well as be able to survive the impacts of long term use. Add to that the need for a stable frequency in most electronic applications, be they digital or analog, and the need for an oscillator circuit capable of consistent performance across process, voltage and temperature variations becomes clear. While there are a variety of possible oscillator designs, one that fulfills the above conditions can be hard to develop. In this project, a low power low voltage relaxation oscillator design is proposed for use in mobile applications. The relaxation oscillator will be capable of wideband performance, up to and exceeding 100MHz, while maintaining its operation on a 1.8V supply at well below 1mA of total current use. The design will also perform consistently across a 0-80℃ temperature range, be independent of supply variation, and will be analysed over different process corners.